Criticism of Reason against the Blasphemy of Ijma as a Source of Islamic Law - Bahrudin, Moh.; Faisal, Faisal; Hanif, Hanif (Universitas Islam Negeri Raden Intan Lampung, 2022)
The study and critique of reasoning against the blasphemy of ijmak aims to place the position of ijmak proportionally and rationally, in accordance with the initial objectives of the ijmak theory formulated in the early days of Islam so that there are no misperceptions about the blasphemy of ijmak. Indeed, ijmak as a source of Islamic law requires the existence of evidence based on the Qur'an and Hadith, it cannot stand alone independently. However, furthermore, ijmak only becomes a support for the status quo of the fiqh laws produced by the cleric contained in fiqh books. This research is intended to look at the blasphemy of ijmak as a source of Islamic law. The method used is descriptive method. Conclusions are drawn by using deductive thinking. Research shows that ijmak can be used as evidence, has validity and authority, although it still requires evidence from the Qur'an or Sunnah. Not all ijmak is qath'i and therefore not all ijmak must be followed. The blasphemy quality of ijmak is qath'i if it is supported by texts that are qath'i or related to matters that are 'ulima min al-din bi al-dharurah. The quality of ijmak is zhanni if it is only supported by zhanni's argument or in matters for which there is no explicit text in the syarak text.